Importance of primary percutaneous coronary intervention for reducing mortality in ST-elevation myocardial infarction complicated by out of hospital cardiac arrest. Issue 4 (1st August 2015) - Choudry, F A; Weerackody, R P; Timmis, A D; Wragg, A; Mathur, A; Sporton, S; Mills, P G; Jain, A K
Abstract: Background: Current recommendations are for primary percutaneous coronary intervention (pPCI) in ST-elevation myocardial infarction (STEMI) complicated by out of hospital cardiac arrest (OHCA). However, information about longer-term outcomes is sparse, particularly among high-risk patients who do not regain consciousness promptly after resuscitation. Methods and results: Of 1836 consecutive patients admitted with STEMI for pPCI between April 2008–October 2011, 132 (7.2%) who had suffered OHCA with recovery of spontaneous circulation (ROSC) form the study population. 101 patients survived to hospital discharge (76.5%) with only one further death in the first year. Prognosis was worse for the 62 patients who were unconscious on arrival and required admission to the intensive therapy unit (ITU), only 54% of whom survived. Every additional minute in the time to ROSC increased the hazard of death by 1.7% while alertness upon ROSC and successful reperfusion in response to pPCI reduced the hazard of death by 90% and 65% respectively. Full neurological recovery was recorded in 85.1% of those who survived to be discharged but in only 30.6% of the 34 survivors who were admitted unconscious and received ITU treatment. Every additional minute in the time to ROSC increased the odds of neurological deficit by 7.0%. Conclusions: In patients with STEMI who are conscious after OHCA, high rates of survival can be achieved with pPCI, depending in part on the time it takes for ROSC. Prognosis is less good in the subgroup brought to hospital unconscious but even in this high risk group neurologically intact survival can be achieved in about one-third of cases, suggesting the benefit of immediate pPCI in STEMI patients successfully resuscitated after OHCA.